Qirâat dan Implikasinya terhadap Penafsiran Ayat-Ayat Hukum dalam Kitab Tafsir Adhwâ’ al-Bayân karya Muhammad al-amin al-Syinqithi - Moh. Sidqie (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of Qirâat (variant Qur’anic readings) on the interpretation of legal verses in Adhwâ’ al-Bayân by Muhammad al-Amîn al-Syinqîthi. Employing a qualitative library research approach, this study examines how both mutawâtir and syâdz Qirâat contribute to the process of Islamic legal deduction (istinbâth). The findings reveal that Qirâat function not merely as linguistic variations but also have significant implications for expanding, reinforcing, and providing flexibility in legal meanings across various domains, including worship (ibadah), family law (munâkahât), transactions (mu‘âmalah), and jihad. Al-Syinqîthi integrates linguistic analysis, textual evidence, and the objectives of Islamic law (maqâṣid al-syarî‘ah) in a comprehensive manner, enabling him to accommodate different Qirâat without generating legal contradictions. Mutawâtir Qirâat serve as the primary foundation for legal rulings, while syâdz Qirâat function as complementary and supportive arguments. This study concludes that the diversity of Qirâat constitutes an integral component of Qur’anic exegesis and Islamic jurisprudence, contributing to the development of a flexible, contextual, and relevant Islamic legal framework.